Improving Students' Speaking Skill In English Lesson Through Action Learning Strategy - Riardila Rumbawa; Vebiyanti Nasir; Sariwati Muhamad (Peneliti.net, 2022)
This research aimed to improve students’ speaking skill in English lesson through Action Learning Strategy. This research was conducted by using pre-experimental design. The subject of this research was XI IPA grade of SMAN Khusus Olahraga consisted of 12 students. This school using K13 as their curriculum and the KKM score was 70. The data was gathered through pre-test and post-test. The result of this research showed that there was increasing of students in speaking skill. The mean of pretest was 67,1 and the mean of 72,7. It indicated that the score of posttests was better than pretest. In the pretest, most of students got scores under 70 which below the KKM score but in the posttest their scores grew up above the KKM. The t-count scores (9,66) also higher than t-table (1,76). So the conclusion is the students’ speaking skill improved and became well when the Action Learning Strategy was implied in English lesson.